Bibliometric Analysis of Global Value Chains in The Agricultural Sector (2024)
The study of global value chains has gained significant importance due to the increasing relocation of productive and commercial activities. Understanding these chains is essential to understand the interconnection of economies worldwide, given that companies are currently integrated into complex networks that span multiple countries and regions. The objective of this research is to carry out a bibliometric analysis of the existing literature on agricultural global value chains (GVCs) using a quantitative approach. For this purpose, a review is conducted in the Web of Science (WoS) database using 341 documents published between the years 2000 and 2023. A performance analysis is carried out, and a cartographic analysis is presented using VOSviewer software. The main findings show a significant growth in research in this field of knowledge since 2018, with 2021 being the year with the highest recorded scientific production. Agricultural CVG show special relevance in economic and environmental areas, with the United States of America being the country with the highest number of publications, and the most relevant research center being the Consultative Group on International Agricultural Research (CGIAR). The trends in the study topic correspond to sustainability, governance, and the scaling up of small producers in global dynamics.  JEL Codes: N50, O13, Q17, Y1 Received: 09/10/2023.  Accepted: 13/05/2024.  Published: 17/06/2024.